Asian and feminist philosophies in dialogue : liberating traditions - McWeeny, Jennifer; Butnor, Ashby (Columbia University Press, 2014)
In this collection of original essays, international scholars put Asian traditions, such as Hinduism, Buddhism, Daoism, and Confucianism, into conversation with one or more contemporary feminist philosophies, founding a new mode of inquiry that attends to diverse voices and the complex global relationships that define our world. These cross-cultural meditations focus on the liberation of persons from suffering, oppression, illusion, harmful conventions and desires, and other impediments to full personhood by deploying a methodology that traverses multiple philosophical styles, historical tex.